Development of a unified clinical trial database for Alzheimer's disease. Issue 10 (9th February 2015) - Neville, Jon; Kopko, Steve; Broadbent, Steve; Avilés, Enrique; Stafford, Robert; Solinsky, Christine M.; Bain, Lisa J.; Cisneroz, Martin; Romero, Klaus; Stephenson, Diane; ,
Abstract: Introduction: Data obtained in completed Alzheimer's disease (AD) clinical trials can inform decision making for future trials. Recognizing the importance of sharing these data, the Coalition Against Major Diseases created an Online Data Repository for AD (CODR‐AD) with the aim of supporting accelerated drug development. The aim of this study was to build an open access, standardized database from control arm data collected across many clinical trials. Methods: Comprehensive AD‐specific data standards were developed to enable the pooling of data from different sources. Nine member organizations contributed patient‐level data from 24 clinical trials of AD treatments. Results: CODR‐AD consists of control arm pooled and standardized data from 24 trials currently numbered at 6500 subjects; Alzheimer's Disease Assessment Scale‐cognitive subscale 11 is the main outcome and specific covariates are also included. Discussion: CODR‐AD represents a unique integrated standardized clinical trials database available to qualified researchers. The pooling of data across studies facilitates a more comprehensive understanding of disease heterogeneity.